Development of a Numerical Regression Model of Gross Domestic Product per Capita Movement in the European Union Member State as a Result of Investments in R&D from the Structural Funds - RajÅ¡p, Matej; Mohar, Lea RobiÄ; PoÅ¾arnik, Matej (International Journal of Economics and Financial Issues, 2020)
This paper examines the movement of gross domestic product per capita (GDP per capita) depending on the normalized value of financial incentives in the field of research and development in the EU-28 Member States. It determines the type of dependence of these variables in the period 2014–2019, evidenced by the Pearson correlation coefficient. Based on empirical data, a mathematical model is formulated that predicts the dynamics of GDP growth in the forthcoming financial perspective 2021-2027 in regard to drawing EU funds. Keywords: European Structural Funds, R&D projects, co-financing, GDP per capita. JEL Classifications: E02; E17; F45; O30 DOI: https://doi.org/10.32479/ijefi.10620